KAJIAN PSIKOLOGI SASTRA NOVEL SORDAM KARYA SUHUNAN SITUMORANG DAN RELEVANSINYA DENGAN PEMBELAJARAN BAHASA INDONESIA DI SMA - Wahidah Nasution; Sarwiji Suwandi; Muhammad Rohmadi (Jurnal Metamorfosa, 2014)
This aims of this research are : (1) Describe and tell the stucture of novel Sordam by Suhunan Situmorang; (2) describe and tell the characters of the main characters in the novel Sordam by Suhunan Situmorang; (3) describe and tell the relevance of the study of novel Sordam by Suhunan Situmorang with learning Indonesian in Senior High School. The conclusions of this research, namely: (1) the structure of the text consists of the characterization study with showing method that can be analyzed through dialogue and the character’s behavior. The second characterization study that is viewpoint technique using the third person who know everything; (2) the main character in the novel Sordam that is Paltibonar with ambitious character, tough, and has a high sense of social. The mother’s character is stubborn. Diandra’s character is obedient to their parents and less patient. Mary’s character is independent; (3) the relevance of study of novel Sordam with learning Indonesian in Senior High School is this novel, its contents suitable with senior high school students as well as the values that contained are taken as a lesson.